Four new species of Dichorisandra J.C. Mikan (Commelinaceae) from Southeast Brazil - Aona-Pinheiro, L. Y.s.; Amaral, M. C.e. (Phytotaxa, 2012)
Based on studies of plants in the field, herbarium, and in cultivation, four new species of Dichorisandra J.C. Mikan are here described. Two of them were collected in Carangola, State of Minas Gerais: Dichorisandra leonii Aona & M.C.E. Amaral, which is similar to D. thyrsiflora J.C. Mikan due to the habit and the position of the anthers in the flower, but differs by the pubescent indument on leaves and stems, and Dichorisandra rupicola Aona & M.C.E. Amaral, growing on rocky outcrops and characterized by its purplish to pinkish anthers, dehiscing by only one pore. The other two species were collected in Espírito Santo State: Dichorisandra velutina Aona & M.C.E. Amaral can be characterized by its velutinous indument on stem, leaf sheath, both faces of the leaf lamina and sepals and by its broad-ellipsoid anthers with truncate apex. Dichorisandra nutabilis Aona & M.C.E. Amaral is similar to D. penduliflora Kunth due to the pendulous inflorescence, but differs by the presence of six stamens with anthers dehiscing by only one pore, while the flowers of D. penduliflora have five stamens with rimose anthers. Illustrations of the species, comparisons with similar species and discussions about diagnostic characters and conservation status of the new species are presented.